Nitrogen fixation by the thermophilic green sulfur bacterium Chlorobium tepidum. - Wahlund, T M (1993)
The thermophilic green sulfur bacterium Chlorobium tepidum grew with N2, NH4+, or glutamine as the sole nitrogen source under phototrophic (anaerobic-light) conditions. Growth on N2 required increased buffering capacity to stabilize uncharacterized pH changes that occurred during diazotrophic growth. Increased sulfide levels were stimulatory for growth on N2. Levels of nitrogenase activity (acetylene reduction) in N2-grown C. tepidum cells were very high, among the highest ever reported for anoxygenic phototrophic bacteria. Maximal acetylene reduction rates in C. tepidum cells were observed at 48 to 50 degrees C, which is about 15 degrees C higher than the optimum temperature for nitrogenase activity in mesophilic chlorobia, and nitrogenase activity in C. tepidum responded to addition of ammonia by a "switch-off/switch-on" mechanism like that in phototrophic purple bacteria. C. tepidum cells assimilated ammonia mainly via the glutamine synthetase-glutamate synthase pathway, elevated levels of both of these enzymes being present in cells grown on N2. These results show that N2 fixation can occur in green sulfur bacteria up to at least 60 degrees C and that regulatory mechanisms important in control of nitrogenase activity in mesophilic anoxygenic phototrophs also appear to regulate thermally active forms of the enzyme.